Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/14651858.cd003968.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological therapies for the management of chronic and recurrent pain in children and adolescents

Abstract: Background This is an update of the original Cochrane review first published in Issue 1, 2003, and previously updated in 2009, 2012 and 2014. Chronic pain, defined as pain that recurs or persists for more than three months, is common in childhood. Chronic pain can affect nearly every aspect of daily life and is associated with disability, anxiety, and depressive symptoms. Objectives The aim of this review was to update the published evidence on the efficacy of psychological treatments for chronic and recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
1
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(203 citation statements)
references
References 115 publications
(408 reference statements)
8
189
1
5
Order By: Relevance
“…Certainly, the authors suggested that different testing paradigms may be affected differently by psychological factors . Nevertheless, psychological treatments might be effective for reducing pain, even when delivered combined with physiotherapy for pain and disability by physiotherapists …”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the authors suggested that different testing paradigms may be affected differently by psychological factors . Nevertheless, psychological treatments might be effective for reducing pain, even when delivered combined with physiotherapy for pain and disability by physiotherapists …”
Section: Discussionmentioning
confidence: 99%
“…Most reviews (n = 19; 40.4%) included variations of mixed chronic pain populations (e.g., abdominal pain, headaches or migraines, widespread pain/fibromyalgia, complex regional pain syndrome, neuropathic pain, sickle cell disease, cancer pain, back pain, and/or pelvic pain). 8,37,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] Reviews focused on single populations most frequently examined abdominal pain (n = 10; 21.3%), 10,35,39,40,57,[59][60][61]77,78 headaches or migraines (n = 5; 10.6%), [62][63][64][65][66] rheumatological conditions (e.g., juvenile idiopathic arthritis, lupus; n = 4; 8.5%), [67][68][69][70] cancer-related pain (n = 3; 6.4%), [71][72][73] or sickle cell disease (n = 2; 4.3%). 74,75 Single reviews focused on patellar tendon pain/Osgood-Schlatter's (n = 1; 2.1%), 76 cerebral palsy (n = 1; 2.1%), …”
Section: Types Of Populationsmentioning
confidence: 99%
“…There are few viable options for prophylactic medications, with many options having limited efficacy or adverse effects . However, behavioral prophylaxis appears to be a valid treatment option for pediatric pain and headache . Specifically, biofeedback is one of the most prominent behavioral approaches, and meta‐analytical evidence suggests that it is effective in treating pediatric migraine …”
Section: Introductionmentioning
confidence: 99%